ANALISIS UNSUR INTRINSIK CERPEN CINTA TAK ADA MATI KARYA EKA KURNIAWAN DAN IMPLIKASINYA DALAM PEMBELAJARAN BAHASA INDONESIA - Cerry Mahera; Ena Noveria (Cendikia: Jurnal Pendidikan dan Pengajaran, 2023)
This research has two objectives. First, to describe the intrinsic elements in the short story Cinta Tak Ada Mati by Eka Kurniawan. Second, to describe the implications of Eka Kurniawan's short story Cinta Tak Mati in learning short story texts. This type of research is qualitative research with descriptive methods. The data of this study are event units in the form of words, phrases, clauses, or sentences that identify the intrinsic elements of the short story in the form of a narrator's narrative about the characters, the actions of the characters, and the speeches of the characters in the setting of the short story Cinta Tak Ada Mati by Eka Kurniawan. The source of the research data is the short story Cinta Tak Ada Mati by Eka Kurniawan which was published by Gramedia in 2018. The results of the research on the short story Cinta Tak Ada Mati by Eka Kurniawan are that there are three characters, namely Mardio, Melatie, and a doctor. The plot in the short story Cinta Tak Ada Mati by Eka Kurniawan is a mixed plot. There are seven elements that develop plot, namely introduction, conflict, complication, climax, crisis, separation, and resolution. The setting in Cinta Tak Ada Mati by Eka Kurniawan is the setting of place, time, and social setting. The point of view used in Eka Kurniawan's Cinta Tak Ada Mati is the third person's point of view. The message conveyed in Eka Kurniawan's Cinta Tak Ada Mati is to gain knowledge that being faithful is good, but if we can't have what we want, it's better for us to leave it so as not to cause wounds and leave grudges behind. Based on the results of this study, it can be concluded that the short story Cinta Tak Ada Mati by Eka Kurniawan can be used as Indonesian language learning material, especially in short story texts.